Comparative Studies of Perianal Structures in Myrmecophilous Aphids (Hemiptera, Aphididae) - Natalia Kaszyca-Taszakowska; Mariusz Kanturski; Łukasz Depa (Insects, 2022)
There are three types of relationships between aphids and ants: non-myrmecophilous, obligatory and facultatively myrmecophilous. The degree of involvement in this mutualism is believed to be corelated with morphological adaptations of perianal structures. In this manuscript, we analyzed the differences of these structures in obligatorily (18 species) and facultatively (10 species) myrmecophilous aphids. Scanning electron microscopy (SEM) and light stereoscopic microscopy (LSM) techniques were used for these studies. Comparison of structures showed no strict relationship between their morphology and the degree myrmecophily, with certain indication that the microsculpture of perianal cuticle may play role in protection of aphids against honeydew droplet in facultatively myrmecophilous aphids.